A small place - Kincaid, Jamaica 1949- (Daunt Books, 2018)
'If you go to Antigua as a tourist, this is what you will see...' So begins Jamaica Kincaid's powerful portrait of the damaged paradise that was her childhood home. The island of Antigua is a magical place of breathtaking beauty - with cloudless skies, dazzling blue waters, and majestic sunsets. But it is also a place of dramatic contrasts. What one doesn't see when on holiday on this ten-by-twelve-mile island in the British West Indies is the sweeping corruption, the dilapidated schools and hospitals and homes, and the shameful legacy of its colonial past. In A Small Place, Jamaica Kincaid candidly appraises where she grew up, and makes palpable the impact of European colonisation and tourism. The book is a missive to the traveller, whether American or European, who wants to escape the banality and corruption of some large place, Kincaid, eloquent and resolute, reminds us that the Antiguan people, formerly British subjects, are unable to escape the same drawbacks of their own tiny realm - that behind the benevolent Caribbean scenery are human lives, always complex and often fraught with injustice. -- From book flap